The Reformist Political Thought of Ahmad Baba al-Timbukti (The International Journal for Scientific Research, 2026)
Ahmad Baba, born in 1556 and deceased in 1627 in Timbuktu, emerged as a prominent scholar who sought to guide individuals away from the path of moral deviation toward the horizons of felicity. Drawing upon his encyclopedic expertise in Islamic jurisprudence, he addressed the intellectual challenges of his time in terms of problematics, epistemological content, and conceptual substance, while simultaneously maintaining a degree of relevance and intelligibility for contemporary readers. The emergence of political thought in Islam coincided with the advent of the Prophetic message in its earliest stages. The revelation of the Qur’an played a decisive role in transforming the intellectual, cognitive, and cultural structures of Muslim society. Consequently, the concepts and meanings associated with political thought became intrinsically linked to the Qur’an and the Sunnah. The Prophet Muhammad (peace be upon him) sought to replace ties of blood and tribal affiliation with the unifying bond of Islam, establishing this bond as a form of political covenant among diverse clans and tribes. Islam thus transcends ethnic and racial distinctions, as expressed in the Qur’anic verse: “Indeed, the most noble of you in the sight of Allah is the most righteous of you.” Within this framework, Ahmad Baba endeavored to reinforce this political covenant between the ruler and the subjects in the Songhai Empire. His thought reflects an inherent dialectic between political theory and practical reality, particularly in light of the assertion of the unity of Sharia and politics since the earliest period of Islam.
Keywords: Ahmad Baba Al-Sudani; Timbuktu; Reformist Political Thought; Songhai Empire